Utilization of Barangay Learning Hub: Framework for Enhancement Program - Rhyann Carlos Balan (Indonesian Journal on Education (IJoEd), 2026)
Educational inequities continue to affect learners from underserved communities due to limited access to technology, academic resources, and supportive learning environments. Community-based learning initiatives such as Barangay Learning Hubs were established to address these challenges and support students’ academic needs. This study aimed to examine the utilization of Barangay Learning Hubs among Junior High School students in the Division of Balanga City and develop an enhancement framework. Guided by a convergent parallel mixed-methods design, quantitative and qualitative data were collected simultaneously using surveys and interviews. Findings revealed that students primarily utilized the learning hub for research, assignments, internet access, and printing services. Students viewed the learning environment, accessibility, and support services positively. However, unstable internet connectivity, overcrowding, limited equipment, and restricted operating hours affected utilization. Qualitative findings further revealed that learning hubs improved academic engagement, digital literacy, and motivation. It is recommended that learning hubs strengthen technological infrastructure, increase resources, and improve operational services to maximize educational support and sustainability.